Sociopragmatic Functions of Sumimasen and Gomennasai in the Film Sayonara no Asa ni Yakusoku no Hana wo Kazarou - Muhammad Nursalam; Meira Anggia Putri (Smart Society, 2026)
Apology expressions play an important role in maintaining interpersonal relationships in Japanese communication. Among the commonly used expressions, sumimasen and gomennasai perform distinct sociopragmatic functions depending on situational context and speaker–listener relationships. However, learners of Japanese often experience difficulty distinguishing the appropriate contexts for using these expressions. Therefore, this study aims to examine the sociopragmatic functions of sumimasen and gomennasai in film dialogue. This research employs a qualitative descriptive approach using sociopragmatic analysis. The data were collected from the animated film Sayonara no Asa ni Yakusoku no Hana wo Kazarou through observation and note-taking techniques. A total of fifteen utterances containing the expressions were identified and analyzed based on their contextual functions. The findings reveal that sumimasen performs two main functions: avoiding conflict and expressing dissatisfaction (two instances) and maintaining attitudinal distance (one instance). Meanwhile, gomennasai appears more frequently and functions as a marker of attitudinal distance (six instances) and as an expression of sincere apology (six instances). These findings suggest that the choice between sumimasen and gomennasai is strongly influenced by interpersonal relationships and emotional context within the narrative interaction.